Characterisation of the Flow and Heat Transfer Behaviour Associated with a Wall-Bounded Dual Jet Flow - Murphy, Paula Jane (Trinity College Dublin. School of Engineering. Discipline of Mechanical & Manuf. Eng, 2024)
The purpose of this investigation is to characterise the fluid flow and heat transfer behaviour of a dual jet comprising a wall jet, discharged immediately parallel to a solid boundary, flowing alongside a parallel jet whose exit is offset from the solid boundary by some distance, i.e., an offset jet. Despite the widespread industrial applications of dual jet flows, which include turbine blade shielding, heat exchangers, fuel injection systems, wastewater evacuation process, air-conditioning, and noise suppression technology, the flow and heat transfer characteristics of a wall-bounded dual jet remains severely underrepresented in the published literature. As a result, the heat transfer capabilities and driving flow mechanisms associated with dual jet flows are not yet fully understood, meaning they cannot be optimised towards specific applications. Most notably, the lack of verified, repeatable experimental flow and heat transfer measurements in the published literature has led to significant discrepancies across the published numerical findings, which furthers the requirement for the provision of a suitable means of validation with simulating dual jet flows. The present study is thus concerned with characterising the transfer of heat to a dual jet flow for varying Reynolds number, offset ratio and velocity ratio through experimental means, as well as acquiring an understanding of the underlying flow phenomena which drive this heat transfer behaviour. The findings of the experimental investigation are hence used to develop a validated numerical dual jet model and improve on the dual jet numerical modelling techniques available in the literature. For the experimental investigation, air is adopted as the working fluid and each jet Reynolds number is varied in the range 5500 ≤ 𝑅𝑒 ≤ 12000, while the offset ratio and velocity ratio are varied in the ranges 1 ≤ 𝑂𝑅 ≤ 7 and 0.5 ≤ 𝑉𝑟 ≤ 2, respectively. The initial heat transfer study subjects the airflow to a constant heat flux generation of 1670 𝑊/𝑚2 in the bounding wall and the surface Nusselt number distribution is measured using infrared thermography techniques. The velocity field is subsequently captured using particle image velocimetry for a more limited offset ratio range of 1 ≤ 𝑂𝑅 ≤ 3, while the range of 𝑅𝑒 and 𝑉𝑟 remain consistent. The results reveal a distinct time-averaged local Nusselt number profile in the wall boundary, where the magnitude and positions of a local 𝑁𝑢𝑥 minimum and maximum can readily be controlled through adjusting 𝑅𝑒, 𝑂𝑅 and 𝑉𝑟 . This is attributed to changes in the size of the recirculation zone, which ultimately dictates the extent of the wall jet deflection and, subsequently, the thickness, length and streamwise position of a small separation region induced adjacent to the solid wall boundary. Analysis of the surface-averaged Nusselt number indicates a linear relationship between ̅𝑁̅̅̅𝑢 𝑥 and 𝑅𝑒, where ̅𝑁̅̅̅𝑢 𝑥 rises linearly with increasing jet Reynolds number, while higher values of ̅𝑁̅̅̅𝑢 𝑥 are noted for lower 𝑂𝑅. The time-resolved flow data indicates the occurrence of periodic vortex shedding, the frequency of which is dependent on 𝑅𝑒, 𝑂𝑅 and 𝑉𝑟 , however, a limited range of unsteady 𝑉𝑟 values are identified. The numerical investigation uses Ansys Fluent 2023 R2 to model an identical dual jet flow configuration by means of the 𝛾 − 𝑅𝑒𝜃 transition model. The numerical data is acquired using a steady state solver for a limited subset of the experimental range of jet parameters, i.e., 5500 ≤ 𝑅𝑒 ≤ 12000, 𝑉𝑟 = 1 and 𝑂𝑅 = 1 and 3. A velocity inlet is applied at the entrance to each jet, where the associated velocity profile, turbulence intensity and turbulent viscosity ratio are tuned appropriately with respect to the experimental data. The results reveal a successful emulation of the experimental heat transfer findings, thus enabling a full validation of the numerical model setup within the accepted uncertainty limits. The numerical model hence introduces significant improvements to dual jet numerical modelling compared to that available in the published literature, despite a slightly slower rate of jet development, where the resulting heat transfer behaviour can be considered more reliable and better aligned with physical reality.
APPROVED
Keywords: particle image velocimetry; turbulent jets; single wall jet; single offset jet; offset ratio; velocity ratio; dual jet; convective cooling; infra-red thermography